HAK WARIS ANAK ANGKAT DALAM SISTEM HUKUM INDONESIA - Adietya Zahrandika Nursetyo; Fitria Agustin (CV. Denasya Smart Publisher, 2026)
The purpose of this study is to examine the legal status of adopted children in the Indonesian inheritance law system and to analyze the various forms of legal protection available for their inheritance rights in the management of inherited assets. The method used is a normative legal approach with a qualitative study through literature analysis, including relevant laws, books, and scientific articles. The results indicate that the legal position of adopted children in the distribution of inheritance in Indonesia is inconsistent, due to the diversity of laws encompassing civil law, Islamic law, and customary law. In the context of civil law, adopted children receive a share through a gift or will; in Islamic law, they are entitled to a mandatory will; while in customary law, adopted children can be treated equally with biological children, depending on the prevailing kinship system in the local community. Legal protection for adopted children's inheritance rights has been regulated in various ways, but in practice, challenges remain, such as low public awareness of inheritance planning and differences in the application of the law. Therefore, it is important to improve legal certainty and public awareness to improve the protection of adopted children in the inheritance context in Indonesia.